Socio-Anthropologic and Genetic Influences on Human Polygyny - Khandoker, Morshed (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Socio-Anthropologic and Genetic Influences on Human Polygyny